Methicillin–resistant Staphylococcus aureus (MRSA) Identification Among Health Care Workers in the Intensive Care of Nusa Tenggara Barat Regional General Hospital - Pristianingrum, Santy; Dasi, Palika Gita Dewi; Zainiati, Baiq Lely; Budi, Endar Trisno; Rahmah, Laila Annisa; Damayanti, Ida Ayu (Jurnal Analis Medika Biosains (JAMBS), 2025)
Healthcare workers (HCW’s) are the primary providers of services in healthcare facilities. The high frequency of contact between healthcare workers and patients renders them susceptible to the transmission of MRSA. This research was conducted to detect the presence of the MRSA using Mec A gene and their sensitivity with antibiotics among HCWs in the intensive care of the Nusa Tenggara Barat Regional General Hospital. This is cross-sectional study with purposive random sampling nostril swabs and information about daily routines of changing outfit HCW’s ICU, HCU, PICU rooms between January-March 2024. The examination included a microbiological examination and a PCR of the Mec A gene.Microbiological examination of 45 HCWs nostril swabs revealed the presence of 31 isolates of S.aureus, 25 of isolate were identified as Methicillin-Susceptible Staphylococcus aureus (MSSA), and 6 as MRSA. Four MRSA isolates from the HCW in ICU exhibited the highest resistant to Cefoxitin (75%), while two HCW’s PICU isolates demonstrated 100% resistant to Amoxicillin. The six MRSA isolates were confirmed positive for the Mec A gene by PCR examination using the Mec A primer at 532 bp, and three of them is a HCW’s who’s didn’t change clothes every day. The presence of the MRSA among HCWs in the intensive care unit of Nusa Tenggara Barat Regional General Hospital was 19%. Furthermore, it was found that all of S.aureus were still sensitif to vancomycin.Test ubah metadata